2014
DOI: 10.1097/mou.0000000000000111
|View full text |Cite
|
Sign up to set email alerts
|

Calcium nephrolithiasis and bone demineralization

Abstract: Patients with recurrent calcium nephrolithiasis and fasting hypercalciuria have a higher incidence of osteopenia and osteoporosis, measured by the dual-energy X-ray absorptiometry. These patients present not only with hypercalciuria and increased BTMs (mainly resorptive), but also up to 30% have hypocitraturia and increased urinary calcium/citrate ratio (>0.25). On the basis of these results, a diagnostic algorithm was created, classifying hypercalciurics according to their fasting calcium/creatinine and calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The urine metabolic profile was interpreted on the basis of the reference values used to assess the mineral metabolism [ 19 , 20 , 21 , 36 ]. At baseline, it was found that potassium excretion was <50 mEq in 90% of the 24 h urine samples, and 85% of women exhibited alteration in pH and/or citrate excretion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The urine metabolic profile was interpreted on the basis of the reference values used to assess the mineral metabolism [ 19 , 20 , 21 , 36 ]. At baseline, it was found that potassium excretion was <50 mEq in 90% of the 24 h urine samples, and 85% of women exhibited alteration in pH and/or citrate excretion.…”
Section: Resultsmentioning
confidence: 99%
“…While the nutritional hypothesis has been amended in systematic reviews and meta-analyses [ 11 , 16 , 17 ], the relationship between renal function, and the risk of osteoporosis or hip fracture has been confirmed in many studies. Recent findings have demonstrated that increased acid excretion [ 18 ], dysregulation of calcium homeostasis [ 19 ] and a decrease in urinary citrate [ 20 , 21 , 22 ] are recognizable in patients who exhibit osteopenia/osteoporosis and high bone turnover, thus, suggesting that urinary metabolic profiling may have significant implications for monitoring bone health status.…”
Section: Introductionmentioning
confidence: 99%
“…Following the first report of a correlation between BMD and KS by Alhava et al [ 21 ], many studies have demonstrated that patients with KS have increased risks of low BMD, osteoporosis, and bone fractures [ 3 , 4 , 22 24 ]. CaKS is considered to be a multisystem disease [ 25 ], and various mechanisms can result in CaKS formation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these [ 105 ] and other authors [ 107 , 108 , 109 , 110 , 111 ] found that patients who formed calcium kidney stones exhibited lower bone mineral density, suggesting that bone demineralization, which often accompanies hypercalcemia [ 112 ], may be linked to calcium stone formation. In fact, a previous study found increased occurrences of osteopenia and osteoporosis in patients with recurrent calcium nephrolithiasis and hypercalciuria [ 113 ]. Interestingly, as Gambaro et al has pointed out, lower bone density has also been linked to abnormal arterial stiffness, partially due to calcification, which is a strong indicator of cardiovascular mortality [ 114 ].…”
Section: Vascular Calcification and Stone Formation Similarities Tmentioning
confidence: 99%